Changes in BQCA Allosteric Modulation of [3H]NMS Binding to Human Cortex within Schizophrenia and by Divalent Cations - Dean, Brian; Hopper, Shaun; Conn, P Jeffrey; Scarr, Elizabeth (Neuropsychopharmacology (New York, N.Y.), 2016)
Stimulation of the cortical muscarinic M1 receptor (CHRM1) is proposed as a treatment for schizophrenia, a hypothesis testable using CHRM1 allosteric modulators. Allosteric modulators have been shown to change the activity of CHRMs using cloned human CHRMs and CHRM knockout mice but not human CNS, a prerequisite for them working in humans. Here we show in vitro that BQCA, a positive allosteric CHRM1 modulator, brings about the expected change in affinity of the CHRM1 orthosteric site for acetylcholine in human cortex. Moreover, this effect of BQCA is reduced in the cortex of a subset of subjects with schizophrenia, separated into a discrete population because of a profound loss of cortical [(3)H]pirenzepine binding. Surprisingly, there was no change in [(3)H]NMS binding to the cortex from this subset or those with schizophrenia but without a marked loss of cortical CHRM1. Hence, we explored the nature of [(3)H]pirenzepine and [(3)H]NMS binding to human cortex and showed total [(3)H]pirenzepine and [(3)H]NMS binding was reduced by Zn(2+), acetylcholine displacement of [(3)H]NMS binding was enhanced by Mg(2+) and Zn(2+), acetylcholine displacement of [(3)H]pirenzepine was reduced by Mg(2+) and enhanced by Zn(2+), whereas BQCA effects on [(3)H]NMS, but not [(3)H]pirenzepine, binding was enhanced by Mg(2+) and Zn(2+). These data suggest the orthosteric and allosteric sites on CHRMs respond differently to divalent cations and the effects of allosteric modulation of the cortical CHRM1 is reduced in a subset of people with schizophrenia, a finding that may have ramifications for the use of CHRM1 allosteric modulators in the treatment of schizophrenia.